The Modern, the Postmodern, and. . . the Metamodern? Reflections on a Transforming Sensibility from the Perspective of Theological Anthropology - Bargár, Pavol (Transformation, 2021)
There have recently been attempts in the academic discourse to describe what is referred to as the demise of the postmodern due to the perceived insufficiency of the latter concept to adequately express the uniqueness of the 21st-century world. The younger generation of scholars, therefore, suggest adopting a new discourse, termed ‘metamodernism’, to do justice to this transforming sensibility. Metamodernism can be characterised by an oscillation between the modern and the postmodern, enthusiasm and irony, hope and nihilism, construction and deconstruction. This article seeks to reflect on this new discourse from the perspective of theological anthropology. It will bring theorists of metamodernism in conversation with theological discussion to explore how Christians can respond and contribute to this ongoing transformation in the human interpretation of reality. It will be suggested that this momentum should be viewed by Christians as a ‘paradigm shift’ that they are to embrace critically, yet affirmatively.